Sikap Pemerintah Aceh Dalam Merespon Penolakan Masyarakat Terhadap Kebijakan Penanganan Covid-19 - Mhd.Reza Pahlewi; Novita Sari; Muliawati Muliawati (Journal of Political Sphere, 2021)
AbstractCovid-19 vaccination is a step that is considered very effective to inhibit the transmission of coronavirus, where the corona virus has a high rate of spread and death. Therefore, the implementation of Covid-19 Vaccination is carried out for free / without any costs that must be borne by the community. This is done as a form of countermeasures against the Covid-19 Pandemic which has a significant impact, especially on the economy and prolonged health. However, efforts in handling the Covid-19 Pandemic there is a rejection, especially in Aceh Province against the implementation of Covid-19 vaccination. This study aims to look at the political attitude of the Aceh government in response to the rejection of the Acehnese people to the Covid-19 vaccination policy through policies or programs carried out to increase the acceptance of acehnese people to Covid-19 vaccination. This research uses public policy theory and the concept of political attitudes. The method used is qualitative with a descriptive approach. The results of this study show the lack of innovation and creativity of the Aceh Government in an effort to increase public acceptance of Covid-19 vaccination. In this case, the Aceh Government is expected to evaluate the programs that have been carried out in response to vaccination rejection in acehnese society, especially against the Covid-19 vaccination socialization program. This is so that the socialization carried out in the future can be carried out better in the people of Aceh.Keywords:Covid-19 Pandemic, Covid-19 Vaccination, Aceh Government Attitude, Public Policy